SIMULATION OF LASER TRANSMITTER BASED ON ND: YAG WITH PASSIVE COOLING FOR RANGEFINDING - K. A. Orehov (Приборы и методы измерений)
Laser emitters used in rangefinders without cooling have several limitations: low energy, high beam divergence at the cavity exit that leads to large output telescope design that significantly increases rangefinder’s size, long time beam parameters instability due to laser crystal heating. In the article laser emitter for a transmitting unit of rangefinder based on cylindrical laser medium Nd:YAG with transverse diode pumping abled to solve all the abovementioned promblems is considered. Matrix optics and balance equations were used for system modeling. The emitter is based on plano-concave scheme cavity with internal concave lens aimed for matching the size of TEM00 mode with the size of laser medium and cavity tuning to stability threshold which allows to achieve divergence of the output pulse at diffraction level for 5 mm diameter medium and 300 mm cavity length. Cavity reconfiguration and mode size compliance is conducted by the longitudinal movement of lens relative to the rear mirror. Three-, twoand one-sided pump schemes are compared in terms of rod energy absorption uniformity and their effectiveness. The three-sided pump scheme model with a system of gold coated reflectors was designed that provides 54 % efficiency of pump when the pump energy is distributed uniformly along the cross-section of the laser medium. Based on the modeling in ANSYS the scheme of laser medium thermal control in vacuum conditions was suggested that implies introduction heat-conducting glue between the side edge of a laser medium and quantron body that allows to low the active medium heating in the 8 min cycle by 35 °С. Beam pulse energy under pump of 1.2 Joule equals to about 0.3 Joule with the 4 ns pulse time and 2 Hz in frequency.